EDUCATION FROM ISLAMIC PERSPECTIVE - Sutiono Sutiono (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2021)
We have confirmed that Islamic education is not the same as the goals of western education, because there are differences in understanding the nature, role, and purpose of human life in the world. This is a very basic problem that is being faced in the world of Islamic education, therefore a solution must be found. The formulation of the goals of Islamic education, one of which is to deliver to the purpose of human creation, which is to become a caliph on earth as stated in the holy book of the Qur'an. The essence of Islamic education is personal development in all its aspects (body, mind, and heart). And is an activity or effort that a person does in order to achieve maximum positive development in humans. The business or activity in question can be in the form of teaching, habituation, giving examples, giving gifts and praise, as well as developing one's knowledge, skills, and life experience. In addition to being interpreted as an activity, education can also be seen as a system. Education as a system is nothing but a functional totality that is directed at one goal. The purpose of education is to achieve the target in accordance with the purpose of creating humans to become caliphs on earth, then the Qur'an and hadith are used as the basis for Islamic education. Steps are needed to reformulate the goals of Islamic education in accordance with the guidance of the Qur'an and Hadith and refer to the Islamic intellectual tradition that has brought glory and prosperity to mankind. Pendidikan Isam sudah kita pastikan tidak sama dengan tujuan pendidikan barat, oleh karena terdapat perbedaan dalam memahami hakikat, peranan dan tujuan hidup manusia di dunia. Ini adalah persoalan yang sangat mendasar yang sedamg dihadapi pada dunia pendidikan Islam, oleh karena itu harus dicari solusinya.Rumusan tujuan pendidikan Islam salah satunya adalah menghantarkan pada tujuan penciptaan manusia, yaitu menjadi khalifah di muka bumi sesuai yang ertuang dalam kitab suci al-Qur’an. Hakikat pendidikan Islam adalah pengembangan pribadi dalam seluruh aspeknya (jasmani, akal, dan hati). Dan merupakan aktivitas atau usaha yang dilakukan seseorang agar tercapai perkembangan maksimal yang positif dalam diri manusia. Usaha atau kegiatan yang dimaksud dapat berbentuk pengajaran, pembiasaan, pemberian contoh dan teladan, pemberian hadiah dan pujian, maupun pengembangan pengetahuan, keterampilan, dan atau pengalaman hidup seseorang. pendidikan selain dimaknai sebagai sebuah aktivitas, dapat juga dipandang sebagai sebuah sistem. Pendidikan sebagai sebuah sistem, tidak lain merupakan suatu totalitas fungsional yang terarah pada satu tujuan. tujuan pendidikan mencapai sasaran sesuai dengan tujuan penciptaan manusia menjadi khalifah di muka bumi, maka al-Qur’an dan hadits yang dijadikan sebagai landasan dalam pendidikan Islam. Perlu langkah untuk merumuskan kembali tjuan pendidikan Islam sesuai dengan tuntunan al-Qur’an dan Hadits serta mengacu pada tradisi intelektual Islam yang telah membawa kegemilangan dan kesejahteraan kepada ummat manusia.